Impact of prooxidant-antioxidant imbalance on the biological age and the rate of aging in arterial hypertension with type 2 diabetes mellitus - V. D. Nemtsova (Zaporožskij Medicinskij Žurnal)
Purpose: to study the state of oxidative-antioxidative balance and its influence on the biological age (BA) and the features of aging in patients with a comorbid course of arterial hypertension (AH) and type 2 diabetes mellitus (T2DM).